Pengaruh Motivasi Belajar, Motivasi Orang Tua, dan Lingkungan Belajar Terhadap Kinerja Mahasiswa Selama Pandemi Covid 19 - Adhelya Ludfy Pratiwi; Maslichah Maslichah; Dwiyani Sudaryanti (Universitas Islam Malang, 2023)
This research is an associative study to analyze the relationship or to determine the effect of Learning Motivation, Parental Motivation, and Learning Environment on Student Performance During the Covid 19 Pandemic. The population in this study were students of the Islamic University of Malang majoring in Accounting and Management from 2016 to 2019. The sampling used in this research is simple random sampling. The results showed that learning motivation had a positive and significant effect on student performance. The higher the level of learning motivation, the more it affects student performance. Parental motivation has a positive and significant effect on student performance. The higher the level of parental motivation, the more it affects student performance. The learning environment has a positive and significant effect on student performance. The better the learning environment, the more it affects student performance. The coefficient of determination R² which shows 0.374, meaning that 37.40% of student performance is influenced by learning motivation, parental motivation, and the learning environment, while the remaining 62.60% of student performance is influenced by other variables not examined in this study.Keywords: Learning motivation, parents' motivation, learning environment, student performance, covid 19 pandemic.